Deference in international human rights law - Legg, A (2011)
Deference in international human rights law has provoked animated discussion, particularly the margin of appreciation doctrine of the European Court of Human Rights. Many commentators describe the practice of deference but do not explain how it affects judicial reasoning. Some approve characteristics of deference but do not provide a justification to defend the practice against criticism. Others regard deference as a danger to human rights because it betrays the universality of human rights or involves tribunals either failing to consider a case properly or missing an opportunity to set human rights standards. This thesis employs a different approach by focussing on deference as the practice of assigning weight to reasons for a decision on the basis of external factors. This approach draws on theories of second-order reasoning from the philosophy of practical reasoning. The thesis offers a conceptual account of deference that accords with the practice not only of the European Court of Human Rights, but also the Inter-American Court of Human Rights and the UN Human Rights Committee. Additionally the thesis presents a normative account of deference, that the role of these tribunals entails permitting a measure of diversity as states implement international human rights standards. Deference in international human rights law then is the judicial practice of assigning weight to the respondent states’ reasoning in a case on the basis of three factors: democratic legitimacy, the common practice of states and expertise. This affects judicial reasoning by impacting the balance of reasons in the proportionality assessment. The account defended in this thesis dispels concerns that deference is a danger to human rights, whilst providing a theory that justifies the practice of the tribunals. The thesis thus provides the contours of a doctrine of deference in each of the three international human rights systems.